Vicon SAGA Platform: An Instrument to Support Collaborative Mapping - Marino, Tiago Badre (2023)
The Vigilance and Control Platform is a Geographic Information System (GIS), free of cost (freeware), based on the philosophy of simplifying the process of collection,storage, and processing of geographic data. In 2000, the system was conceived by Geographer Jorge Xavier da Silva, founder, and coordinator of the UFRJ GeoprocessingLaboratory. With the purpose of representing, in a georeferenced database, all the events and entities of an environment, it differs from other existing applications for its flexibility in the preparation of forms, according to the peculiarities inherent to the theme of each task. The present text, organized chronologically, describes the history of the creation and evolution of the Vicon SAGA Platform, from its conception to the present day, supporting the collection and processing of environmental data in more than 1,200 applied research projects throughout the country.